Microbial healing of cracks in concrete: a review - Joshi, S.; Goyal, S.; Mukherjee, Abhijit; Reddy, M. (Springer Link, 2017)
Â© 2017, Society for Industrial Microbiology and Biotechnology. Concrete is the most widely used construction material of the world and maintaining concrete structures from premature deterioration is proving to be a great challenge. Early age formation of micro-cracking in concrete structure severely affects the serviceability leading to high cost of maintenance. Apart from conventional methods of repairing cracks with sealants or treating the concrete with adhesive chemicals to prevent the cracks from widening, a microbial crack-healing approach has shown promising results. The unique feature of the microbial system is that it enables self-healing of concrete. The effectiveness of microbially induced calcium carbonate precipitation (MICCP) in improving durability of cementitious building materials, restoration of stone monuments and soil bioclogging is discussed. Main emphasis has been laid on the potential of bacteria-based crack repair in concrete structure and the applications of different bacterial treatments to self-healing cracks. Furthermore, recommendations to employ the MICCP technology at commercial scale and reduction in the cost of application are provided in this review.